NILAI-NILAI KEPEMIMPINAN PADA PONDOK PESANTREN RASYIDIYAH KHALIDIYAH AMUNTAI KALIMANTAN SELATAN - Wahyudin Wahyudin; Muhniansyah Muhniansyah; Muhammad Zakiyyul Fuad Rasyid (CV. Adiba Aisha Amira, 2025)
Objective: This study aims to identify and describe leadership values at the Rasyidiyah Khalidiyah Islamic Boarding School in Amuntai, South Kalimantan. Methodology: The research method used was a qualitative approach with a case study design. Sampling techniques were carried out using targeted sampling and snowballing techniques. The research instruments used were observation, interviews, and document examination. Data analysis was conducted using an inductive conceptualisation approach. Findings: Based on the research conducted, the following findings were obtained regarding leadership values at the Rasyidiyah Khalidiyah Islamic Boarding School in Amuntai: (1) Types of values: the main values at the Rasyidiyah Khalidiyah Islamic Boarding School in Amuntai are sincerity, kinship, togetherness, and boarding school values (morals and rituals). (2) Sources of values: The leadership values of the Rasyidiyah Khalidiyah Amuntai Islamic Boarding School originate from the founder of the boarding school (muassis), leadership figures, and teachers at the boarding school. (3) Transmission of values, at the Rasyidiyah Khalidiyah Amuntai Islamic Boarding School, values are transmitted within the cultural environment of the boarding school, which is reinforced by traditions such as haulan, selamatan, rituals, ceremonies, and the practice of ‘gawi sabumi’ work. (4) Awareness of values, there is a strong awareness among members of the basic principles. These values determine academic leadership and organisational actions. (5) Value advancement: this study shows that the dissemination of values within the organisational community occurs naturally and continuously, built within a unique environment of interaction and coloured by the nature of the leadership. (6) Documentation of values: the main social values possessed and developed in Islamic boarding schools are not documented, but new organisational leadership values have been written normatively and textually in institutional documents.